2010
DOI: 10.1111/j.1540-6261.2010.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

The Net Benefits to Leverage

Abstract: I estimate the market's valuation of the net benefits to leverage using panel data from 1994 to 2004, identified from market values and betas of a company's debt and equity. The median firm captures net benefits of up to 5.5% of firm value. Small and profitable firms have high optimal leverage ratios, as predicted by theory, but in contrast to existing empirical evidence. Companies are on average slightly underlevered relative to the optimal leverage ratio at refinancing. This result is mainly due to zero leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
172
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(220 citation statements)
references
References 61 publications
31
172
0
9
Order By: Relevance
“…Unlike existing studies that use traditional cross-sectional or panel regressions using observed leverage ratios 6 , the threshold model allows us to determine optimal leverage despite firms' temporary deviations from the optimum. Again, we reach conclusions similar to those of Korteweg (2010).…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Unlike existing studies that use traditional cross-sectional or panel regressions using observed leverage ratios 6 , the threshold model allows us to determine optimal leverage despite firms' temporary deviations from the optimum. Again, we reach conclusions similar to those of Korteweg (2010).…”
Section: Introductionsupporting
confidence: 76%
“…This suggests a positive relationship between profitability and optimal leverage. Bearing in mind that this result is not a formal test of the trade-off theory, the conclusion is nevertheless qualitatively similar to the theoretical prediction of the trade-off theory and the empirical results of Korteweg (2010).…”
Section: Firm Characteristics and Optimal Leveragesupporting
confidence: 70%
See 2 more Smart Citations
“…This variability arises as these …rms choose considerably di¤erent levels of optimal debt due to their dissimilar fundamental characteristics. In order to shed further light on this …nding, we study the importance of the di¤erent primitive features of 1 In related papers, van Binsbergen, Graham, and Yang (2010) and Korteweg (2010) report that the net bene…ts of debt account for 3.5% and 5.5% of …rm value, respectively.…”
Section: Introductionmentioning
confidence: 99%